To React or Not to React: The Dilemma of Fish Immune Systems Facing Myxozoan Infections - Holzer, Astrid S.; Piazzon, M. Carla; Barrett, Damien; Bartholomew, Jerri L.; Sitjà-Bobadilla, Ariadna (Frontiers in Immunology, 2021)
Myxozoans are microscopic, metazoan, obligate parasites, belonging to the phylum Cnidaria. In contrast to the free-living lifestyle of most members of this taxon, myxozoans have complex life cycles alternating between vertebrate and invertebrate hosts. Vertebrate hosts are primarily fish, although they are also reported from amphibians, reptiles, trematodes, mollusks, birds and mammals. Invertebrate hosts include annelids and bryozoans. Most myxozoans are not overtly pathogenic to fish hosts, but some are responsible for severe economic losses in fisheries and aquaculture. In both scenarios, the interaction between the parasite and the host immune system is key to explain such different outcomes of this relationship. Innate immune responses contribute to the resistance of certain fish strains and species, and the absence or low levels of some innate and regulatory factors explain the high pathogenicity of some infections. In many cases, immune evasion explains the absence of a host response and allows the parasite to proliferate covertly during the first stages of the infection. In some infections, the lack of an appropriate regulatory response results in an excessive inflammatory response, causing immunopathological consequences that are worse than inflicted by the parasite itself. This review will update the available information about the immune responses against Myxozoa, with special focus on T and B lymphocyte and immunoglobulin responses, how these immune effectors are modulated by different biotic and abiotic factors, and on the mechanisms of immune evasion targeting specific immune effectors. The current and future design of control strategies for myxozoan diseases is based on understanding this myxozoan-fish interaction, and immune-based strategies such as improvement of innate and specific factors through diets and additives, host genetic selection, passive immunization and vaccination, are starting to be considered.